An Assessment of Concurrent Jurisdiction and Claim of Ownership of Trademarks under OAPI Legislation - Dashaco Akuriah, Nelson (International Multilingual Journal of Science and Technology, 2025)
Trademarks are economic tools that aid businesses to communicate with their customers and capture a vast section of the population. Trademarks are only useful when used efficiently in the course of trade, meaning the higher the reputation of the mark, the more consumers want to associate themselves to the products or services the mark is affixed upon. This study examines the criteria to own a trademark and how ownership claims are handled between the African Organisation of Intellectual property as known by its French acronym OAPI and the competent domestic courts found at the level of Member States which has become a breathing ground for confusion in the resolution of disputes. Due to both bodies having concurrent jurisdiction in dispute resolution, the cost has become unbearable on trademark owners or beneficiaries of an exclusive license of exploitation, coupled with inconsistency in judgements from the two structures. The article highlights some key improvements expanding trademark subject matter and provides information on how the two institutions cited above handle matters of jurisdiction based on case law. The article also brings to the limelight how the OAPI administrative litigation bodies can collaborate with the competent domestic courts to arrive at clear and concise decisions. In conclusion the paper provides some recommendations on bridging the gap between both jurisdictions in order to attain the objectives of all parties involved.
Keywords: Concurrent Jurisdiction; Intellectual property; Litigation; Ownership; Registration; Trademarks; Use

Fairness, Digital Markets and Competition Law – Reconciling Fairness Norms in Digital Markets Act, Data Act and AI Act with Competition Law - Kianzad, Behrang (Journal of Law, Market & Innovation, 2025)
The present article explores the implication of fairness as a regulatory and competition law concept applied to digital and Artificial Intelligence markets, in light of recent law and policy developments targeting the interaction between data, market power and competition law. Much of the policy discussions, legislative proposals as well some emerging case law elevate the matter of “fairness” in the context of digital markets and AI, creating both a novel regulatory framework as well as encouraging competition law to curb “unfairness” of said markets and related “unfair practices”. The interface between intellectual property rights and competition law is of utmost importance in this context, where we might find similar analogous insights as we can find regarding the matter of fairness within traditional EU competition law. Further, the question remains whether the “fairness norm” expressed in regulatory acts such Digital Markets Act, EU AI Act and the EU Data Act are akin to the “fairness” norms found in Union competition law, mainly under Article 102 Treaty on the Functioning of the European Union (TFEU).

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

Islamic Law Aspect on in Valuation and Execution Intellectual Property (IP) Asset as Bank Collateral in Creative Economy - Margono, Suyud (International Journal of Social Science Research and Review, 2024)
One of the issues faced by many creative economy actors in this relatively newly established industry is the lack of supporting infrastructure, such as the limited access to financing and one of the prominent issues is banks’ reluctance to accept intellectual property (“IP”) as collateral to secure loans including problems concerning valuation of IP Asset as Collateral which has implications several regulation concerning Intellectual Property. In the spirit of furthering the creative economy, the Government has recently issued Government Regulation Number 24 of 2022 on Intellectual Property-Based Creative Economy Financing. This matters includes in relation with IP assets that are exposed and exploited their product (goods or services) on the basis of exclusivity in financing and loan contractual scheme as collateral. This article normative legal research in which intended for studies that are literary and practical works which is Intellectual Property (IR) system in relation with valuation and execution as bank collateral either Indonesia prevailing law and Islamic (Syariah) Law. The result of this research that IP owners often deal with complex contractual relationships that involve different forms of cooperation in research, production or commercialization. most important aspect concerning capacity and competency with comprehensive knowledge deal with IP Asset as Collateral before Banks, and others financial institution, execution of guarantees as applied to Islamic banking has adopted many syariah law, in the practice, there are still many problems the implementation of guarantees as applied to Islamic banking has adopted many Islamic laws. However, in the practice, there are still many problems that arise from the Islamic law scope the concept of justice and the philosophy of maslahah.
Keywords: Creative Economy Valuation and Execution Asse; Intellectual Property (IP) Collateral; Islamic (Syariah) Law

Summary survey on publishing contract in the OAPI space - Ngombé, Laurier Yvon (The Journal of World Intellectual Property, 2024)
The OAPI member states constitute a space for theharmonization of copyright in Africa. This harmonizationis yet to be completed, as attested by the conventionalrules relating to the publishing contract. In addition,investigating about the publishing contract in the OAPIspace requires an examination of both the text of theBangui Agreement and that of the national laws of the 17member states. Some differences must be pointed outkeeping in mind the question of possible conflict of laws.
Published by John Wiley & Sons Ltd.
Keywords: ARIPO; Conflict of laws; Contract; Copyright

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
URI: https://scholar.sun.ac.za/handle/10019.1/128896
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Infringement of Brand Rights on Different Products Is an Illegal ACT - Fahdia, Khamada Wafi; Roisah, Kholis (International Journal of Social Science Research and Review, 2023)
The study aims to find out how the provisions of the law are in violation of brand rights to nongender products and their protective forms, as well as how legal efforts should be made in violation of their laws. Legal protection for legitimate brands' owners is regulated within brand laws intended to give their owners exclusive rights. Legal measures that rights holders can make on broken brands can be made either by civil law or criminal law. Indonesia's brand registration system is a constituent system, and it is recommended that all efforts be quick to register a trademark or service brand for the creditor of intellectual property rights. The holding of a brand would be wise to appeal to the court immediately if there is any indication that a brand offense is committed by another and the cost is not greater.
Keywords: Brands Infringement; Products of No Kind; Unlawful Conduct

Analysis of Intellectual Property Rights Disputes Between PS Glow and MS Glow in View of Law No. 20 of 2016 Concerning Marks and Geographical Indications (Analysis of Decision of Case Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby) - Gracia, Indiera Fortuna; Kurniawan, Kurniawan; Sili, Eduardus Bayo (International Journal of Social Science Research and Review, 2023)
This study analyzes intellectual property rights disputes between PSGlow and MSGlow in terms of Law no. 20 of 2016 concerning Trademarks and Geographical Indications (analysis of case decision number: 2/pdt.sus.HKI/Merek/2022/pn.niaga Sby) which aims to explain and analyze the basic considerations of Surabaya Commercial Court judges in accepting lawsuits, explaining and analyzing how is the legal protection of trademarks that have been registered based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications, explaining and analyzing whether there is an element of passing off between PS Glow and MS Glow based on Case Decision Number: 2/Pdt.Sus.HKI /Merek/2022/PN. Niaga Sby.The legal materials in this research are primary, secondary, and tertiary legal materials using normative research methods.The basis for consideration is that a lawsuit was filed from PS Glow for the use of the brand without rights against MS Glow. and legal protection for brands that have been registered under Law no. 20 of 2016 concerning Marks and Geographical Indications, namely that the penalties that will be imposed on these counterfeiters can be in the form of imprisonment, imprisonment and fines, as referred to in articles 100 to 102 of Law No. 20 of 2016 concerning Marks and Geographical Indications. and between PS Glow and MS Glow there is no element of passing off based on Case Decision Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby, because the MS Glow brand registers its brand in HAKI in class 32 with the classification of powdered drinks and PS Glow registered their brand on Intellectual Property Rights in class 3 with a cosmetic classification.
Keywords: Brand; IPR; Passing off

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
URI: http://hdl.handle.net/10019.1/127343
Keywords: Antitrust law; Australia; Competencia; Competition Act; 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

Legal Protection of Trade Secret from the View of Civil and Criminal Law - Atika, Atika (International Journal of Social Science Research and Review, 2023)
Indonesia has ratified the WTO/TRIPs Agreement convention and is in full compliance and non-reservation, the insistence of developed countries’ owners of Intellectual Property Rights against Indonesia, and the need for national Intellectual Property Rights. By looking at the above, legal protection is needed for every product and service, especially licenses for trade secrets in the Intellectual Property Rights component. The state imposes criminal sanctions on violators of Trade Secret rights as stipulated in chapter 17 (1) constitution number 30/2000. However, it is also hoped that the act of imposing sanctions by the state will return to the interests of the protected party by making the crime a complaint offense chapter 17 (2) constitution number 30/2000. There are repressive legal actions that can be carried out as chapter 11 constitution number 30/2000 states that the holder of trade secret rights or the licensee may sue anyone who deliberately or without rights commits the actions referred to in the article in the form of (a). Compensations claim and/or; (b). Cessation of all actions referred to in chapter 4 constitution number 30/2000.
Keywords: Intellectual Property Rights; Legal Protection; Trade Secrets

Intellectual Property Law in Africa: Harmonising Administration and Policy - Ncube, Caroline B. (Taylor & Francis, 2023)
Examining the harmonisation of Intellectual Property policy, law and administration in Africa, this book evaluates the effectiveness of efforts to establish continental Intellectual Property institutions and frameworks. It also considers sub-regional initiatives led by the regional economic communities and the regional Intellectual Property organisations, focusing on relevant protocols and agreements that address Intellectual Property as well as the implementing institutions. The book assesses the progress of such initiatives with particular reference to the current socio-economic status of African states. It argues that that harmonisation initiatives need to be crafted in a way that is supportive of the developmental goals of African states and advocates for due consideration of individual states’ unique conditions and aspirations. This book will be of great relevance to scholars and policy makers with an interest in Intellectual Property law and its harmonisation in Africa.
Accepted: 2023-06-22T09:36:20Z
Keywords: Africa; Droit (harmonisation); Intellectual property; Public interest; TRIPs; governance; thema EDItEUR::G Reference

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels

Three Essays on Digital Platforms and Competition Policy - Yan, Jun (Université Toulouse 1 Capitole, 2022)
Cette thèse se compose de trois chapitres indépendants et examine différentes questions antitrust liées aux plateformes de gatekeeper. Le chapitre I explore le problème du verrouillage vertical dans les marchés bifaces. Dans le cadre des Accelerated Mobile Pages (AMP) de Google, le chapitre 2 examine la question de l'accès des plates-formes de contrôle d'accès aux données des utilisateurs professionnels. Le chapitre 3 se concentre sur le droit d'auteur numérique et étudie le comportement de Google consistant à utiliser le contenu des éditeurs pour afficher des réponses courtes sur les pages de résultats de recherche.Le premier chapitre examine comment l'intégration verticale d'une plate-forme monopolistique, qui se caractérise par des externalités de réseau bilatérales entre groupes, influe sur son incitation à s'engager dans le verrouillage en aval. Je me concentre sur un environnement où la plate-forme et les vendeurs en aval sont confrontés à l'incertitude quant aux gains du commerce au stade de la passation des marchés. Le choc aléatoire étant non contractile, la contractualisation crée des frictions qui faussent la structure tarifaire de la plateforme. En revanche, l'intégration verticale atténue ce problème en permettant à la plate-forme d'intégrer le choc aléatoire des prix à la consommation. En raison de l'interaction entre la friction des transactions et les externalités de réseau intergroupes, je trouve que l'intégration verticale pourrait réduire l'incitation de la plate-forme à la forclusion.Le deuxième chapitre est un travail conjoint avec Doh-Shin Jeon. Nous étudions comment l'adoption par les journaux d'AMP, un format de publication qui permet le chargement instantané de pages Web dans les navigateurs mobiles, modifie l'allocation des données et, par conséquent, les incitations des journaux à investir dans un journalisme de qualité. L'adoption d'AMP permet à Google d'obtenir des données sur les consommateurs à partir d'articles AMP et de les combiner avec d'autres sources de données sur les consommateurs pour améliorer le ciblage des publicités diffusées par Google sur d'autres sites Web. Même si une telle combinaison de données augmente l'efficacité statique, elle peut réduire l'efficacité dynamique lorsqu'elle diminue les revenus publicitaires par trafic de journal, réduisant ainsi la qualité du journalisme. Les journaux sont confrontés à un problème d'action collective car l'adoption de l'AMP par un journal génère des externalités négatives pour les autres journaux via le classement des recherches et la fuite de données. Google peut tirer parti de son pouvoir de marché dans la recherche et l'intermédiation publicitaire pour inciter les journaux à adopter AMP. Nous fournissons des recours politiques.Le troisième chapitre construit un modèle théorique de biens d'information divisibles pour examiner comment l'utilisation d'extraits par un moteur de recherche monopolistique impacte la consommation et la création de contenu. En affichant des extraits dans la zone de réponse sur les pages de résultats de recherche, le moteur de recherche dissocie les informations essentielles et les informations supplémentaires des articles. Elle crée donc deux effets opposés sur l'incitation des éditeurs à investir dans la qualité : l'effet de taille du marché et l'effet d'élasticité. Son impact sur le bien-être social est ambigu. D'une part, la boîte de réponse améliore l'efficacité de la recherche en offrant un accès plus large aux informations essentielles et en permettant aux consommateurs inframarginaux de substituer les informations essentielles à l'article complet. D'un autre côté, cela pourrait réduire le trafic sur le site Web, réduire les revenus publicitaires des éditeurs et les inciter à investir dans la qualité. J'examine les impacts des différentes politiques qui obligent le moteur de recherche à payer pour l'utilisation d'extraits.
Keywords: Antitrust law; Competencia; Competition Policy; Competition law; Concurrence; Concurrence (droit); Digital Platforms; Economie des médias; Google; Intellectual property; Marché biface; Media Economics; Online Advertising; Plateformes digitales; Propriedade intelectual; Propriété intellectuelle; Publicité en ligne; Technologies de l'information et de la communication – Aspect économique; Two-Sided Market

EU copyright reform : an institutional approach - Mangal, Natasha (Université de Strasbourg, 2022)
Cette thèse a pour objet d’étudier comment le dispositif institutionnel actuel pour l’adaptation du droit d’auteur dans l’Union européenne peut être reconsidéré afin de promouvoir le niveau de cohérence plus élevé dans les pratiques réglementaires des États membres, ainsi que dans l’intérêt de la promotion d’un corps de règles européennes plus dynamiques en la matière.À l’aide de l’outil normatif de l’analyse institutionnelle comparative, les dispositions institutionnelles actuelles sont examinées, en se concentrant sur la qualité de la participation des parties prenantes du droit d’auteur dans le système politique, le marché et les tribunaux. Des exemples d’institutions administratives du droit d’auteur dans certaines juridictions (États-Unis et Canada) sont analysés plus en détail, en tirant des conclusions sur leurs fonctions et leurs rôles dans leurs systèmes juridiques respectifs. Enfin, cette thèse propose plusieurs solutions politiques, y compris la possibilité d’envisager une nouvelle autorité au niveau de l’Union européenne pour le droit d’auteur. En fin de compte, la remise en question du statu quo institutionnel dans l’Union européenne peut révéler de nouvelles voies prometteuses pour développer les fonctions administratives, quasi judiciaires, d’observation et de conseil nécessaires à la gestion du droit d’auteur à l’ère du numérique.
Keywords: Analyse institutionnelle comparative; Comparative Institutional Analysis; Copyright; Digital Single Market; Droit de la propriété intellectuelle; Droit d’auteur; Droits d'auteur; Institutions; Intellectual property; Intellectual property law; Marché unique numérique; Union européenne

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

Hyperlinking and copyright - Karjiker, Sadulla (The South African Law Journal, 2022)
This article critically considers the legality of hyperlinking to copyright-protected material on the Internet. It considers the position with respect to standard hyperlinks, and attempts to provide a possible approach in light of the proposed introduction of two new exclusive rights, namely (i) the right of communication to the public; and (ii) the making-available right. These new exclusive rights appear to be an attempt to amend the South African Copyright Act in order to give effect to the 1996 WIPO Copyright Treaty, which sought to ‘digitise’ copyright law in light of the digital technology that had developed. The WIPO Copyright Treaty supplements, in particular, the rights granted to copyright owners under the Berne Convention, extending the right of communication to the public to include the making-available right. Use will be made of the case law of the Court of Justice of the European Union, which has given effect to the right of communication to the public (including the making-available right), following its inclusion in the WIPO Copyright Treaty of 1996. Through a more focused analysis of these exclusive rights, it is intended that this article can provide some guidance to South African lawyers and our courts when considering the application and scope of these exclusive rights.
Keywords: Copyright; Hyperlinking; Intellectual property; Legality

Reasonable awareness in compensation for infringement of IP rights - Vanbrabant, Bernard; Glorieux, Dietger (Revue de Droit Intellectuel. L'Ingenieur-Conseil, 2021)

The impact of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) on the right to health and the right to development: a study of the implementation of TRIPS in Zimbabwe - Munemo, Ropafadzo Blessing (University of KwaZulu-Natal, 2021)
The right to health and the right to development are intertwined socio-economic rights that affect the well being and growth of a country’s populace. Most developing and least developed countries face challenges in ensuring access to essential medicines vis a vis the realisation of the right to health and full potential of development. Patents, provided for under the TRIPS Agreement are partly to blame for the lack of access to essential medicines as they account for the excessive pricing of medicines. Zimbabwe being a developing country currently facing dire economic and political challenges but being obliged under the International and Regional Human Rights Conventions it subscribed to, has to ensure the progressive realisation of the right to health and development. However, as a member of the TRIPS Agreement, there are limitations to the country’s ability to ensure access to medicines and healthcare for developmental purposes. This thesis has outlined the problematic provisions of the TRIPS Agreement and Zimbabwe’s attempt to use the flexibilities provided to its advantage. Zimbabwe has only put into use the flexibility of compulsory licensing and parallel importation to a limited extent; hence the recommendation that even though the country has domesticated the Agreement to its advantage, the country needs to explore other flexibilities comprehensively and promote the realisation of the rights to health and development.
Keywords: Access to medicine; Health care costs; Intellectual property; Public health; TRIPs; Trade tariffs; Zimbabwe

Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch University, 2020)
The maxim, that copyright law does not protect ideas, is frequently challenged when the established principles are tested against new forms of expression or exploitation of a work. The evolution of computer programs, its unique characteristics and the increasing value of software as a commodity have resulted in a strained relationship between copyright law and the public interest regarding access to the underlying ideas in a computer program. This work examines the misalliance between copyright principles and the technical nature of computer programming, with a specific focus on the act of decompiling an existing program where it is undertaken in order to understand the underlying ideas and techniques. The impetus for this analysis is the sui generis classification of computer programs in South African copyright law and the potential this offers for development of domestic law in pursuit of national policy goals. This work conducts a normative analysis of the law and the technical reality of decompilation, from the perspective that copyright law must maintain a clear separation between the idea and the expression. The review of national and foreign copyright law is, throughout, conducted with a perspective on the effect of protection and a critical examination of the degree to which the law maintains an adequate balance between the private and public interests in the protection of software. In this respect, the current legal position is evaluated and a different, normative and prodevelopmental perspective regarding decompilation is proposed. It is submitted that are balancing of interests is justified and essential in order to establish an appropriate level of fairness and, at the same time, stimulate progress in this industry. It is argued that the act of using computer code to discover its meaning should not amount to infringement in the form of reproduction or adaptation of the work. It is found that the perception of decompilation, as a form of infringement, relies on an analogy to literary work. This view, it is argued, is ill suited to the nature of computer programs, at odds with the sui generis classification in SA copyright law, causes overbroad protection and violates the idea/expression separation. In light of the technical review of decompilation, it is found that the legal basis for prohibiting decompilation as a form of infringement is narrower than commonly assumed and that copyright law principles should be reinterpreted purposefully to permit decompilation. This work advocates that decompilation must be permissible and that an exemption, in SA copyright law, which is limited to decompilation for interoperability alone, is not appropriate in light of the national developmental agenda. Therefore, an alternative exemption is proposed which accommodates the technical reality of decompilation, the public interest in access to ideas and the commercial interests of copyright owners. This approach is supported by an analysis of international copyright law and is based on the inherent flexibilities of the three-step test. The justification for the findings of this work and the proposed departure from foreign precedent is supported by a close examination of the effect of a limited decompilation exception in foreign law and the impact of legislative measures to restrict circumvention of technological protection measures.
URI: http://hdl.handle.net/10019.1/109088
Keywords: Copyright; Copyright infringement; Decompilation; Intellectual property; International Copyright

Protecting the Industrial Designs of Today and the Future - Samoylov, Vladimir (Victoria University of Wellington, 2020)
This study examines and critiques New Zealand intellectual property protection for industrial designs, taking into account that many New Zealand industrial design owners outsource manufacture of their designs to China. Industrial design, which refers to improving the aesthetics of products to increase their marketability, is evolving conceptually and practically. In New Zealand, copyright and registered design laws each protect, respectively, the visual expression and the “eye appeal” of an original design. As design practices evolve with advances in technology however, it is increasingly evident that industrial design is about more than just visual expression or “eye appeal”. Many designers are not focusing solely on product stylisation and decoration, but on the provision of a more holistic product experience for the consumer. The development process of industrial designs from concept to marketable product is also changing, with many New Zealand industrial design owners employing increasingly efficient design development strategies. The fast-paced, cost-effective infrastructure of China is often utilised by New Zealand businesses for the manufacture of industrial designs. This study therefore sought to determine how to appropriately protect New Zealand industrial designs, in light of: a. foreseeable advances in technology; and b. the fact that many New Zealand industrial designs are manufactured in China. To answer these questions, this study examined and analysed New Zealand’s copyright and registered design laws, taking into account not only existing protections, but also factors that are likely to be of significant relevance in the future, such as the impact on industrial design from developments in 3D printing and virtual reality. The Chinese intellectual property regime for industrial designs was also examined because China is a major trading partner and often, as noted, the locus of manufacture. The study included an empirical investigation, in the form of interviews with designers and design academics as well as legal practitioners specialising in intellectual property law. The input of the interviewees, together with the legal analysis, informed a series of suggestions and recommendations for New Zealand policy and its law-makers regarding how industrial design protection can be improved. A key finding of this study was that existing legal protections do not appropriately protect increasingly holistic designs, as well as new types of designs emerging from developing fields such as virtual reality. In assessing the appropriateness of protection, the interests of industrial design owners were balanced against the public interest in protecting the public domain. It is suggested that to achieve equilibrium copyright law should be expanded to protect design expressions for all senses. Moreover, new categories of copyright protected works should be introduced to accommodate emerging design. The definition of design in registered design law should also be reconceptualised in order to acknowledge new types of designs and evolving design practices. Industrial design owners who outsource manufacturing to China can protect their designs via copyright as well as design patent. However, enforcement of intellectual property protection is unsatisfactory in many areas of China. Therefore, New Zealand industrial design owners should also employ non-legal protection strategies. Interviews with successful businesses, in the course of the empirical investigation for this study, revealed that the leveraging of existing relationships of those with already established operations in China, and intentionally splitting an industrial design’s component parts for manufacture among several factories in different locations, are useful strategies to employ.
Keywords: 3D printing; Artistic Craftsmanship; China; Copyright; Doing business in China; Intellectual property; Multisensory Designs; Propriedade intelectual; Propriété intellectuelle; Registered design; Spare Parts; Virtual Designs; Virtual Reality

Rights on news : expanding copyright on the internet - Furgal, Urszula (European University Institute, 2020)
The internet and digital technologies have irreversibly changed the way we find and consume news. Legacy news organisations, publishers of newspapers, have moved to the internet. In the online news environment, however, they are no longer the exclusive suppliers of news. New digital intermediaries have emerged, search engines and news aggregators in particular. They select and display links and fragments of press publishers’ content as a part of their services, without seeking the news organisations’ prior consent. To shield themselves from exploitation by digital intermediaries, press publishers have begun to seek legal protection, and called for the introduction of a new right under the umbrella of copyright and related rights. Following these calls, the press publishers’ right was introduced into the EU copyright framework by the Directive on Copyright in the Digital Single Market in 2019.
Accepted: 2020-02-20T11:26:15Z
Keywords: Copyright; Digital media; Electronic information resources; Intellectual property; Internet; Propriedade intelectual; Propriété intellectuelle

Protection of Intellectual Property Rights in International Trade - Indradewi, Anak Agung Sagung Ngurah (International Journal of Social Sciences, 2020)
That intellectual property is the creation of ideas in the form of new discoveries, literary works, and works of art, symbols, names and images used in trade. Of course, intellectual property is closely related to the world of commerce because its emergence is triggered by the desires of the members of the World Intellectual Property Organization who want to protect their economies in the era of free trade. In this case how the form of protection of intellectual property rights in the perspective of international trade, it can be seen that basically the laws and or regulations in every country in the world are different and each country has the right to implement its own legal rules in the jurisdiction of their country.
Keywords: Intellectual property; Intellectual property rights; International Trade; Legal rules

The copyright protection of musical works : a historical and contextual analysis - Baloyi, Jele Joel (University of South Africa, 2019)
This work is concerned with an analysis of the copyright protection of musical works. Musical works form part of the categories of works protected under copyright law. It would be easy to dismiss musical works as not warranting a serious study, as would for example, be warranted for “industrial property” rights such as patents and geographical indicators, or more “serious” copyrights such as architectural works and computer software. Such a perspective would however, not be cognisant of the significant contribution that the music industry, as part of the broader cultural and creative industries makes to the global economy. It has, for example, been shown that in 2013, the global cultural and creative industries contributed some US$2,250b, employing some 29,5 million people, with the music industry being one of the top three employers and with its revenues exceeding those of radio.1 A single successful musician can earn in excess of US$100m per annum,2 making the industry ripe for litigious claims. For this reason therefore a consideration of the legal rules that apply to the protection of musical works is crucial. There is currently no clear exposition and systematic analysis of the legal principles applicable to the field of music copyright and no work devoted to the in-depth delineation of the rights and sub-rights relating to musical copyright protection. This study seeks to address this research and knowledge gap by providing a historical and contextual analysis of the protection of musical works. The aim is to provide a complete picture of the milieu of music copyright protection to enable the reader to feel empowered in dealing with the subject-matter. This the writer does by mapping the historical development of music copyright protection in particular from eighteenth century England when the first copyright legislation was enacted, until the enactment of the British Copyright Act of 1911, which signalled the emergence of the “common law” copyright system. The writer then shows how this enactment shaped the development of modern music copyright law, and concludes by presenting a contextual consideration of the current South African law of music copyright and highlighting the challenges it is faced with.
Keywords: Copyright; Copyright protection; Dramatico-musical works; Imperial Copyright Act; Intellectual property; Intellectual property rights; Music; Music trade; Musical compositions; Musical works

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Copyright as a constraint on creating technological value - Drążewski, Kasper (European University Institute, 2019)
How do we legislate for the unknown? This work tackles the question from the perspective of copyright, analysing the judicial practice emerging from case law on new uses of intellectual property resulting from technological change. Starting off by comparing results of actual innovation-related cases decided in jurisdictions with and without the fair use defence available, it delves deeper into the pathways of judicial reasoning and doctrinal debate arising in the two copyright realities, describing the dark sides of legal flexibility, the attempts to ‘bring order into chaos’ on one side and, on the other, the effort of judges actively looking for ways not to close the door on valuable innovation where inflexible legislation was about to become an impassable choke point. The analysis then moves away from the high-budget, large-scale innovation projects financed by the giants of the Internet era. Instead, building upon the findings of Yochai Benkler on the subject of networked creativity, it brings forth a type of innovation that brings together networked individuals, sharing and building upon each other’s results instead of competing, while often working for non-economic motivations. It is seemingly the same type of innovation, deeply rooted in the so-called ‘nerd culture’, that powered the early years of the 20th century digital revolution. As this culture was put on trial when Oracle famously sued Google for reuse of Java in the Android mobile operating system, the commentary emerging from the surrounding debate allowed to draw more general conclusions about what powers the digital evolution in a networked environment. Lastly, analysing the current trends in European cases, the analysis concludes by offering a rationale as to why a transformative use exception would allow courts to openly engage in the types of reasoning that seem to have become a necessity in cases on the fringes of copyright.
Accepted: 2019-01-14T15:17:37Z
Keywords: Copyright; Fair use (Copyright); Intellectual property

The challenge of three-dimensional printing : questioning established concepts in intellectual property law - Elam, Viola (European University Institute, 2019)
Over the last years, academics, practitioners and policy makers have focused their attention on an emerging technology: three-dimensional printing (“3DP”). 3DP is often portrayed as a game changer, showing the potential to disrupt established socioeconomic paradigms and exert profound implications in disparate areas of law. 3DP not only is well integrated in the manufacturing industry, but also increasingly adopted at consumer level. Recent developments have made it possible for ordinary people to take an active role in the production, customization and distribution of goods, and likewise paved the way for the proliferation of new market entrants, such as 3DP online platforms. Against this background, this thesis aims to shed some light on the implications that 3DP may have for Intellectual Property Law. In particular, this work attempts to predict and grasp the consequences that the digitization of real world things may carry in the area of IP law, both from the side of protection and infringement. This contribution is intended to create general awareness about the current state of the art and likewise delineate possible future scenarios in the 3DP ecosystem. The research question at the core of the analysis is whether the current legal framework of different IPRs already offers suitable means for regulating the thin dividing line between the digital and the analogue world, or rather needs to be amended, in order to cope with such a fascinating reality. To this end, the analysis contributes insights to the best legal treatment that CAD files shall receive, in case such files embed products protected by copyright, designs, patents and trademarks. Hence, it addresses right owners’ concern that the online transmission of CAD files, combined with the ease of converting such files into the final printout, will facilitate mass-scale and worldwide infringement of all IPRs.
Accepted: 2019-01-15T14:09:48Z
Keywords: 3D; Copyright; Intellectual property; Three-dimensional printing

Relations between quality of trademarks and cognitive and conative variables of consumers - Naumovski, Goce (Université de Strasbourg, 2018)
But de la recherche : déterminer la dépendance des caractéristiques des marques (perceptibilité visuelle, représentation graphique, le caractère distinctif, non-généricité etc.), sur les types généraux spécifiques de capacités intellectuelles et sur les caractéristiques conatives des consommateurs de la population générale, par application de nombreux tests. La recherche a été réalisée sur un échantillon de 206 sujets-consommateurs. Ils ont évalué la qualité des marques de commerce (déposées et refusées) pour différents types de produits et services (TM-1 test). Les sujets ont été testés avec 3 tests cognitifs et 6 tests conatifs. Méthodes quantitatives appliquées : paramètres élémentaires de la statistique descriptive ; corrélation ; analyse factorielle ; analyse de régression multivariée, analyse canonique des corrélations. Les résultats ont indiqué que les variables cognitives et conatives ont des relations statistiquement significatives avec les résultats de TM test (qualité des marques).
Keywords: Capacités cognitives; Caractéristiques conatives; Cognitive abilties; Comportement des consommateurs; Conative characteristics; Consommateur; Consumers; Intellectual property; Marques; Marques de commerce (droit international); Propriété intellectuelle (droit international); Trademarks

Enabling intellectual property and innovation systems for South Africa's development and competitiveness - Sibanda, McLean (University of South Africa, 2018)
During the last two decades, there have been a number of policy and legislative changes in respect of South Africa’s intellectual property (IP) and the national system of innovation (NSI). In 2012, a Ministerial Review of the Science, Technology and Innovation (STI) landscape in South Africa made recommendations to improve the STI landscape and effectively the national system of innovation. The study provides a critical review of drafts of the national IP policy published in 2013 as well as the IP Framework released in 2016 for public comment. The review of the IP and the NSI are within the context of the National Development Plan (NDP), which outlines South Africa’s desired developmental goals. South Africa is part of the BRICS group of countries (Brazil, Russia, India, China and South Africa). The South African economy is characterised by a desire to move away from being dependent on resources and commodities, to becoming a more knowledge based and innovation driven economy. It is hoped that such a move would assist the country to address some of the social and economic development challenges facing South Africa, as captured in the NDP. South Africa has a functioning IP system, but its relationship with South Africa’s development trajectory is not established. More particularly, the extent to which the IP system relates to the innovation system and how these two systems must be aligned to enable South Africa to transition successfully from a country based on the production of primary resources and associated commodity-based industries to a viable knowledge-based economy is unclear. The Trade-related Aspects of Intellectual Property Rights (TRIPS Agreement) of the World Trade Organisation (WTO) provides that IP must contribute to innovation and to transfer of technology and knowledge in a manner that is conducive to social and economic welfare. Certain provisions set out the foundations of intellectual property systems within the context of each member state. This study has thus explored the complex, complementary and sometimes contested relationships between IP and innovation, with particular emphasis on the potential of an intellectual property system to stimulate innovation and foster social and economic development. The study has also analysed the interconnectivity of IP and innovation with other WTO legal instruments, taking into account South Africa’s positioning within the globalised economy and in particular the BRICS group of countries. The research involved a critical review of South Africa’s IP and innovation policies, as well as relevant legislation, instruments, infrastructure, IP and innovation landscape, and relationship with international WTO legal instruments, in addition to its performance, given the developmental priorities and the globalised economy. The research documents patenting trends by South Africans using European Patent Office (EPO), Patent Cooperation Treaty (PCT), United States Patents and Trademarks Office (USPTO) databases over the period 1996-2015. A comparative analysis of patenting trends amongst BRICS group of countries has also been documented. The study also documents new findings, observations and insights regarding South Africa’s IP and innovation systems. Some of these, particularly in relation to higher education and research institutions, are directly attributable to the Intellectual Property Rights from Publicly Financed Research and Development Act. More particularly, the public institutions are becoming relevant players in the NSI and are responsible for growth of certain technology clusters, in particular, biotechnology. At the same time, the study makes findings of a decline of private sector participation in patenting as well as R&D investment over the 20-year period. Recommendations are included regarding specific interventions to ensure coherence between the IP and innovation systems. Such coherence and alignment should strengthen the systems’ ability to stimulate innovation and foster inclusive development and competitiveness, which are relevant for addressing South Africa’s socio-economic development priorities.
Keywords: BRICS; Biopharmaceutical; Biotechnology; Commercialisation; Economic development; Flexibilities; Inclusive growth; Innovation; Intellectual property; Licensing; Patents; Start-ups; TRIPs Agreement

Virtual property : towards a general theory - Pałka, Przemysław (European University Institute, 2017)
The primary contribution of the thesis is a theory enhancing the legal understanding of the phenomenon of virtual property, encompassing presentation of data and a new conceptual framework to interpret it. The author argues that the normative debates concerning the phenomenon have underestimated the importance of understanding and conceptualizing it first, and aims at amending this gap. The ‘virtual property phenomenon’ refers to the users of internet platforms and online computer games ‘possessing’ virtual items – digital objects that exist within these services – and getting into economic and social relations concerning these items, with other users, service providers and third parties. These relations are regulated by different types of service-specific rules – contractual and the ‘code’ – created unilaterally by the service providers, who additionally retain the ability to interpret and enforce them, using ‘digital force’, i.e. by modifying and deleting virtual items, and blocking users’ accounts. The primary challenge stems not from the fact that the phenomenon is not regulated, but from the fact that lawyers lack words – terms and concepts – to even conduct a meaningful debate about it, or how to respond to it. The thesis consists of six chapters. Firstly, the author describes the phenomenon and analyzes the theoretical and regulatory legal challenges posed by its emergence. Secondly, he critically assesses the state of the art. Thirdly, a methodology to address these challenges is proposed, which can also be used in other research projects concerning law and technology. Fourthly, the author explains how the process of digitalization has fundamentally challenged the assumptions that private law held about the structure of reality, and proposes new doctrinal tools to conceptualize it. Fifthly, the author presents a legally useful concept of virtual items, and argues that granting users property rights over them might not be the optimal means of realizing the property goals. Finally, the author proposes a normative solution, a correction of private law, responding to the new type of inequality in relations, namely a user protection law.
Accepted: 2017-12-21T14:08:02Z
Keywords: Computer games; Internet; Possession (Law); Property

Libraries in the digital renaissance law and policy for book digitization - Panezi, Argyri (European University Institute, 2017)
This dissertation examines the phenomenon of book digitization and the legal challenges for the creation of digital libraries. It explores whether the current copyright framework supports libraries in the digital era as they strive to remain the institutional guardians of our literary treasures. The thesis hypothesis is that the current framework is unsuccessful or inadequate in supporting libraries. To test this hypothesis and identify the legal inefficacies the dissertation examines context, i.e. the history and rationale for applying copyright rules to books and libraries, the copyright rules as applied to libraries before and after digitization was possible, various digitization projects and the practical challenges that digitization brought about, and, the relevant litigation which has started on both sides of the Atlantic covering over a decade now. Furthermore, the thesis explores normative directions of copyright rules, including their exceptions, applicable to libraries in the digital era. It ultimately proposes that among various players claiming this role, libraries, given their institutional functions and capabilities, should be attributed rights to digitization and a favorable legal framework for providing access to digital material.
Accepted: 2018-01-08T09:36:41Z
Keywords: Copyright; Digital libraries; Electronic data processing; Electronic information resources; Intellectual property; Propriedade intelectual; Propriété intellectuelle

'You wouldn't steal a car' vs 'information wants to be free' : regulatory failure of copyright law through the prism of systems theory - Gracz, Katarzyna (European University Institute, 2016)
The thesis aims at explaining current regulatory crisis of copyright law (understood as its inability to regulate social dynamics as regards production, reproduction, dissemination of and access to information goods) through the application of systems theory. It refers to the concept of autopoietic legal system in order to draft a model representing the ecosystem in which copyright law functions. This model not only allows for observing copyright regime as it stands currently but also for analysing how it evolved over time. It scrutinises the interdependencies between the legal system and other constituent elements of its ecosystem: politics, economy, art, science, technology, religion, mass media, education as well as non-functionally differentiated segments of society: circles of relatives and friends. The main goal of this analysis is to highlight the fact that the current regulatory crisis of copyright is the result of the legal system's failure to equally acknowledge all the diverse rationalities constituting its ecosystem. The primary hypothesis of the study is that the core of the problem may be attributed to the divergence between legal norms, and competing non-legal copynorms constructed in the process of co-evolution within various elements of the model in question. In the analysis all the relevant copynorms understood as segmented social norms regulating social dynamics with respect to production, reproduction, dissemination of and access to information goods have been reconstructed to indicate their potential to oppose legal regulations. The thesis pivots around the concept of reflexive justice which refers to the equal acknowledgement of colliding rationalities. It concludes with the firm statement that copyright law in the digital environment needs profound reform. The concept of reflexive justice as developed within the systems theoretical approach is perceived by the author of this thesis as the most promising starting point for the new philosophy of copyright law.
Accepted: 2016-05-17T13:43:06Z
Keywords: Copyright; Intellectual property; Sociological jurisprudence

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

Designing justice: a critical analysis of intellectual property rights within the fashion industry - Parbhoo, Sade (University of KwaZulu-Natal, 2016)
Designers are those individuals within our society with a desire and drive to create. In general designers can be found in all facets of industry and good designers (and ultimately good designs) are the very backbone upon a successful business is built. Designers are required to marry practical knowledge with artistic ability and we are reliant on their skills and to turn abstract ideas into formal designs for everything from the groceries we purchase, the cars we drive and of course, the clothes we wear. Whilst there is no definitive delineation of what a fashion design is, generally fashion designs relate to the creation of designs that focus on clothing, apparel and accessories. The style and functionality of the end products rest firmly within particular time frames, economic and socio-cultural environments within which particular designers find themselves. Accordingly the fashion design industry is never one that stagnates but rather is one that is constantly evolving. In South Africa, the fashion industry is blossoming. As an emerging economy, it is important to create opportunities and not barriers for entry into particular sectors for emerging entrepreneurs. The entire fabric of the fashion industry has certainly changed over time and these changes have brought an increased focus on issues of copying and counterfeiting. It is the contention of some in the industry that there is a need for stricter protection of the actual design in and of itself. Using intellectual property rights as a means of protecting fashion designs is very fitting as every new design begins with an idea, which then evolves, though a process of creative engagement and application of skill and labour to become the final original end product. Designers seeking to protect their designs would need to consider the provisions of the Copyright Act, the Designs Act and the Trade Marks Act. These Acts may in some instances provide a means for protect the actual design incidentally, i.e. by protecting the designer‟s rights in relation to reputation and goodwill associated with the goods whilst in others may afford protection to the design itself. The focus of this research will be a discussion of the legal mechanisms available to fashion designers in South Africa for the protection of their designs using their intellectual property rights and an assessment of whether the fashion industry is in need a stronger intellectual property regime than the current one.
Keywords: Design protection; Fashion industry; Intellectual property; Ownership; Retail trade; South Africa

The Economics of tort law applied to Internet intermediaries : example of intellectual property - Lefort, Marine (École nationale supérieure des mines de Paris, 2015)
La responsabilité des intermédiaires d'Internet fait débat dans un univers numérique de plus en plus complexe. Les intermédiaires offrent des services en ligne. Ils créent ou facilitent des transactions entre des parties tierces (hébergement, e-commerce, fournisseurs d'accès…). A la fin des années 1990, un consensus s'est établi sur l'instauration d'une responsabilité limitée pour ces acteurs, dans le but de favoriser leur développement ainsi que celui d'Internet par des externalités croisées. Cependant, l'apparition régulière de nouveaux usages a induit des externalités négatives affectant certains agents économiques. La multiplication récente de décisions de jurisprudence parfois contradictoires, en particulier dans le domaine de la propriété intellectuelle, vient désormais remettre en cause cette exemption. Elle fait naître un risque juridique pour les intermédiaires d'Internet. Ces-derniers doivent alors prendre en compte ce nouveau contexte dans leurs modèles d'affaires. Notre recherche étudie les comportements spécifiques que la responsabilité des intermédiaires d'Internet engendre à travers l'exemple de la propriété intellectuelle. En premier lieu nous décrivons l'évolution historique de cette responsabilité. Nous développons ensuite un modèle théorique simple qui explore l'influence du risque légal dans un contexte de concurrence entre un intermédiaire et un ayant droit du copyright. Enfin nous étendons ce modèle de concurrence aux différents comportements de protection que peuvent choisir les intermédiaires.
Keywords: Competencia; Competition law; Concurrence; Economie du droit; Intellectual property; Intermédiaires d’Internet; Internet; Internet intermediaries; Law and Economics; Propriedade intelectual; Propriété intellectuelle

Equal treatment as a principle to guide the regulation of intangibly transferred content : a case study on e-books using the examples of copyright exhaustion, reduced rates of VAT and fixed book pricing - Linklater, Emma (European University Institute, 2015)
Using e-books as a case study, this thesis considers whether the principle of equal treatment could play a role in driving more consistent and rational regulation of markets where content is available in both tangible and intangible formats. At present, although the content is the same, these formats are often subject to different rules. This difference in treatment has opened up discussions about whether current legal frameworks should be amended and in these discussions actors with very different standpoints have consistently invoked the language of equality to justify their varied stances. However, in these discussions there is no clear elaboration of what equality means or how it can be used, leading to abstract debates and eventually to arbitrary decisions. The thesis attempts to fill this gap by building a framework based on outcome equality to decide if intangible book formats should be treated ‘like’ tangible ones. It uses the objective underlying the existing rule as the standard for establishing likeness or difference and advocates that functional equality, rather than formal equality, is desirable because this takes account of the differences in the functionalities between content formats: Intangibility impacts on the functioning of the rule in question (e.g. quantitatively increased ease of circulation and copying) and it is only if these impacts can be neutralized that functional equality can be achieved. The framework is applied to the case studies of copyright exhaustion, reduced rates of VAT and fixed book pricing. These have been chosen in recognition of the range of decision-making powers between the national and EU levels in this cultural sector. Overall, the analysis shows that rationality can be inserted by using equal treatment as a guide, but that consistency is more difficult to achieve given the interaction between national and EU influences in the book market.
Keywords: Copyright; Cultural policy; Electronic publishing; European Union countries; Intellectual property

Challenges of Transnational Trademark Law Practice: The Case of Nigerian Companies’ Brands in OAPI States - Nwabueze, Caroline (Revue générale de droit, 2015)
Nigeria industrial growth has turned the country into an indispensable economic support for its neighbours. Only for the case of Cameroon, Nigeria has been the leading supplier with respectively 22% and 17.8% of imports in 2011 and 2012 with trade amounting to 328 billion FCFA per annum. This results in part from Nigerian companies’ exportations in local markets. Nigerian trademarks related to cosmetics, furniture, electronics, and pharmaceutical goods abound in neighbouring countries. However, a strengthening of Nigerian companies in regional markets encompasses strategies to avoid infringing on the trademark rights. Such strategies should include the consideration of special trademarks features by different institutions of the intellectual property (IP) system in the relevant neighbour export markets. This is by the mere fact that the legal status of those goods, although physical property, relies mainly on the material law applicable, which is trademark in the present case. Because the principle of territoriality requires that trademark protection be sought in the place where the goods are sold—and trademark applications filed in each country in which protection is sought—, Nigerian companies planning to outsource some business activity in neighbour markets will seek compliance with trademarks norms applicable in the Organisation africaine de la propriété intellectuelle (OAPI) of which those countries—Benin, Cameroon, Chad, and Guinea—are part. The trade partnership between companies from a common law trademark background on one hand, and civil law intellectual property community on the other, inevitably raises some frictions and trademarks issues. This article analyses the trademark challenges arising from Nigerian companies’ business decision to enter OAPI markets and export goods and services. The article firstly underlines the issues to be taken into consideration, including registration and enforcement of the companies’ marks in OAPI. Then the paper simultaneously reviews the dissimilarities issues between the Nigerian Trademark Act and the OAPI Trademark System to which the Nigerian companies are confronted. If trademark protection makes it easier for an enterprise to access transnational markets, the establishment of a Trademark Community with neighbouring countries helps for sure national industries to establish partnerships with other firms for sustainable development in the areas such as production, marketing, distribution or delivery of goods and services. In light of the trademark harmonisation in the European Union internal market, the present paper concludes by recommending the creation of a Trademark Community in the West and Central African region between Nigeria and its neighbouring countries. La croissance industrielle du Nigeria a fait de ce pays un soutien économique indispensable pour ses voisins. Pour ne citer que l’exemple du Cameroun, le Nigeria en a été le principal fournisseur avec respectivement 22 % et 17,8 % des importations en 2011 et 2012 et des importations dont la valeur s’élève à 328 milliards fr. cfa par année. Ceci résulte en partie des exportations des compagnies nigérianes vers les marchés locaux. Les marques de commerce nigérianes dans le domaine des cosmétiques, des meubles et des produits électroniques et pharmaceutiques abondent dans les pays voisins. Cependant, le renforcement des compagnies nigérianes dans les marchés régionaux englobe des stratégies pour éviter d’enfreindre les droits de propriété industrielle et commerciale. Dans le cadre de ces stratégies, les différentes institutions qui régissent la propriété intellectuelle (PI) dans les marchés d’exportation des pays voisins pertinents devraient prendre en compte des caractéristiques particulières relatives aux marques de commerce. Ne serait-ce que du simple fait que le statut juridique de ces produits, bien qu’ils soient des biens physiques, repose principalement sur le droit substantiel applicable, le droit de la marque de commerce dans ce cas. Parce que le principe de territorialité nécessite que la protection de la marque de commerce soit demandée dans le territoire où les biens sont vendus, et que cette protection doit être demandée dans chaque pays individuellement, les compagnies nigérianes qui prévoient externaliser des activités commerciales dans des marchés voisins chercheront à se conformer aux normes en matière de marques de commerce qui sont applicables au sein de l’Organisation africaine de la propriété intellectuelle (OAPI), dont font partie le Bénin, le Cameroun, le Tchad et la Guinée. Le partenariat commercial entre des entreprises soulève inévitablement, et ce, tant du point de vue de la common law que celui du droit civil, des frictions et des problèmes lorsqu’il s’agit de marques de commerce. Le présent article analyse les défis relatifs aux marques de commerce découlant de la décision commerciale des entreprises nigérianes de faire leur entrée dans les marchés de l’OAPI et d’y exporter des biens et services. L’article souligne premièrement les problèmes qui doivent être pris en considération, dont l’inscription et la mise en application des marques des entreprises membres de l’OAPI. Ensuite, ce texte examine simultanément les problèmes résultant des différences entre la Nigerian Trademark Act et le système de marques de commerce de l’OAPI, système auquel les entreprises nigérianes sont confrontées. Si la protection des marques de commerce facilite l’accès aux marchés transnationaux pour les entreprises, la mise en place, avec les pays voisins, d’une communauté en matière de marques de commerce aide assurément les industries nationales à établir des partenariats avec d’autres entreprises dans le but d’assurer un développement durable dans des domaines tels que la production, la commercialisation, la distribution ou la livraison de biens et services. À la lumière de l’harmonisation des marques de commerce dans le marché intérieur de l’Union européenne, le présent article conclut en recommandant la création d’une communauté de marques de commerce dans la région de l’Afrique occidentale et centrale, et qui réunirait le Nigeria et ses pays voisins.
Keywords: Afrique occidentale; Commerce transnational; Communauté de marques de commerce; Community trademark; Compagnies nigérianes; Enforcement; Intellectual property; Marque déposée; Mise en oeuvre; Nigerian companies; OAPI; Principe de territorialité; Principle of territoriality; Propriedade intelectual; Propriété intellectuelle; Trademark practice; Transnational trade; Western Africa

The sui generis and intellectual property protection of expressions of folklore in Africa - Nwauche, Enyinna Sodienye (North-West University, 2015)
This thesis articulates an optimum framework for the protection of expressions of folklore in Africa using a number of African countries – South Africa, Kenya, Ghana and Nigeria as case studies. This thesis argues that the existing sui generis and intellectual property rights protection in African countries are grossly inadequate in protecting expressions of folklore in these countries. An optimum framework for the protection of expressions of folklore would constitute a combination of the positive and negative protective model elaborated and implemented through a human and people's rights framework that recognises that communities that produce expressions of folklore should own and control how their intellectual property is protected. While a positive protective model explores how intellectual property rights such as copyright, trademarks, designs and performances may protect expressions of folklore through the endowment of such rights on communities, negative protective models examine how state and national competent authorities protect expressions of folklore on behalf of communities. An optimum framework for the protection of expressions of folklore recognises that regional and international perspectives are critical for the protection of folklore in third party countries and expressions of folklore that occur in contiguous countries. A regional perspective is important for Africa countries because of two regional intellectual property organisations in Africa (ARIPO – African Regional Intellectual Property Organisation) and OAPI (African Intellectual Property Organisation) that have established minimum standards for the protection of expressions of folklore. Norm setting and standards in international organisations such as WIPO (World Intellectual Property Organisation); UNESCO (United Nations Educational Cultural and Scientific Organisation); and the WTO (World Trade Organisation) significantly impact the protection of expressions of folklore in Africa. A human and peoples' rights framework explores how national and regional legal systems in Africa recognise entitlements of communities in the protection of the expressions of folklore they produce. In this regard, the normative framework of communities in terms of their customary law is also explored.
Keywords: ARIPO; African Regional Intellectual Property Organization; Communities; Customary law; Expressions of folklore; Ghana; Indigenous people; Intellectual property; Intellectual property rights; Kenya; Nigeria; Peoples' rights; South Africa; Sui generis; WIPO; World Intellectual Property Organization

Economies of scope, modularity and property rights in software technologies - Özaygen, Altay (Université Evry-Val-d’Essonne, 2013)
Cette thèse étudie le rôle des différents régimes de propriété intellectuelle (DPI) et évalue ses conséquences sur l'industrie du logiciel. En outre, ce travail porte sur l'équilibre entre deux modèles de logiciels, celui des logiciels privés et celui des logiciels libres et open source, et cherche à évaluer leurs effets sur la performance des entreprises. Ainsi nous discutons dans un premier article les facteurs clés de la cinquième révolution technologique à travers le concept de paradigme technoéconomique (Freeman et Perez, 1988) et nous considérons l'open source comme le principal de ces facteurs. D'autre part, nous étudions les trois aspects des technologies logicielles. Les caractéristiques structurelles des logiciels, c'est-a-dire les économies de gamme (Panzar et Willig, 1981; Teece, 1980) et la modularité (Parnas, 1972; Langlois et Robertson, 1992) représentent les deux premiers. Le régime de propriété intellectuelle, qui est a l'origine des particularités institutionnelles du logiciel (Mazzeloni et Nelson, 1998b), représente le troisième aspect. Au sein de cette thèse nous utilisons différentes méthodologies et considérons plusieurs technologies logicielles pour répondre à nos questions de recherches. Les économies de gamme de logiciels sont étudiées à travers une simulation multi-agents. La recherche sur la modularité est effectuée par une analyse des brevets sur la technologie d'indexation de vidéo. La question des DPI est examinée dans deux chapitres différents. Dans un premier chapitre, une analyse de données de panel est faite pour démontrer l'effet du brevetage et de la contribution au projet du noyau Linux sur la performance des entreprises. Le second chapitre traite quant à lui d'un cas particulier où l'innovation ouverte est réalisée par un groupe de recherche en ingénierie du logiciel au sein d'Alcatel-Lucent Bell Labs, Nozay, France. Ces exemples uniques ne peuvent conclure sur aucune tendance macro sur l'industrie du logiciel, mais cette thèse vise à alimenter les discussions sur les droits de propriété intellectuelle au sein de l'industrie du logiciel.
Keywords: Analyse de brevets; Industrie – Logiciels; Intellectual property; Logiciels libres; Modularity; Open source; Propriedade intelectual; Propriété intellectuelle; Software industry

Copyright : rebalancing the public and private interests in the areas of education and research - Wang, Jia (Stellenbosch University, 2013)
The general public should have wide access to copyrighted materials for education and research. However, since the current copyright law system subtly favors copyright holders, it is time to re-evaluate copyright law to ensure it meets its original purpose of promoting the learning of the society. The research primarily focuses on how to broaden copyright limitations and exceptions for the public to access and use learning materials. Within the framework of the copyright law system, other mechanisms that allow users to access copyrighted materials at a reasonable price also are considered. Such mechanisms include an efficient collective copyright management system and various licensing schemes. In an information network environment, it is time for developing countries to reform copyright law in order to promote education and research. It is hoped the findings of this study not only benefit South Africa and People's Republic of China, but also provide insights and guidelines to other developing countries with similar conditions.
URI: http://hdl.handle.net/10019.1/85834
Keywords: China; Copyright; Economic aspects; Education and copyright law; Effect of copyright on ICT; Freedom of information and opinion; Globalization and education; Information and communication technology; Intellectual property; South Africa

Open-source software and the rationale for copyright protection of computer programs - Karjiker, Sadulla (Stellenbosch University, 2013)
The rationale for the legal protection of copyright works is based on the perceived need to encourage the creation of works which are considered to be socially beneficial. By awarding authors proprietary rights in their creations, copyright law allows authors the ability to earn direct financial returns from their efforts, and, thus, copyright law provides the required incentives for authors to create copyright works. Since the early days of commercial software development, copyright protection has been extended to computer programs; thus, by providing such protection it was assumed that their production should be encouraged, and that without such protection they will not be produced to the extent required by society. Comparatively recently, we have witnessed large-scale production of open-source software, which is licensed on generous terms, giving users the right to freely use, modify and redistribute such software. By adopting such licensing terms, the authors of open-source software are unable to charge licensees a fee for permission to use their software, which is the reward which copyright assumes authors seek to create such software. This development has made it necessary to re-evaluate the rationale for copyright protection of computer programs, and determine whether the continued protection of computer programs is justifiable. This study seeks to first establish a coherent theoretical justification for copyright protection, which it is submitted should be an economic justification, rather than a moral justification. The legal analysis in this work seeks to establish whether the copyright protection of computer programs is consistent with the economic justification for copyright protection. In particular, the analysis focuses on the current scope of copyright protection, and seeks to establish whether such protection is excessive, stifling creativity and innovation, and, thus, imposing too high a social cost. It is contended that copyright doctrine has generally sought to minimise these costs, and that current scope of copyright protection of computer programs leaves enough creative room for the production of new software. Despite the fact that the effect of open-source software licences is that authors are unable to earn the direct financial rewards which copyright enables authors to earn as an incentive to create such software, their authors continue to have financial incentives to create such software. Commercial firms who invest in open-source software do so because they seek to provide financially-rewarding related services in respect of software, or because it serves to promote sales in their complementary products. Similarly, the participation of individual computer programmers is largely consistent with the standard economic theories relating to labour markets and the private provision of public goods. Individuals are principally motivated by economic motives, such as career concerns. Copyright protection gives participants the choice to opt for the direct financial rewards which its proprietary protection enables, or the more indirect financial rewards of open-source software development. It is submitted within this research that rather than undermining the rationale for copyright protection of computer programs, the development of open-source software has illustrated that copyright protection allows for the emergence of alternative business models, which may be more economically advantageous to authors.
URI: http://hdl.handle.net/10019.1/80044
Keywords: Computer programs; Copyright law; Intellectual property; Open-source software

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification

Users' entitlements under the fair dealing exceptions to copyright - Shay, Richard Michael (Stellenbosch University, 2012)
This thesis analyses current South African copyright law to ascertain the proper interpretation and application of the fair dealing provisions contained in the Copyright Act 98 of 1978. Copyright law ensures that authors’ works are not used without their consent, which they can grant subject to compensation or conditions attached to the use. Fair dealing exceptions allow the general public to use copyright works for certain purposes without the copyright owner’s consent and without paying compensation. These provisions are intended to balance copyright owners’ interests with the interest that members of the public have in using copyright works for socially beneficial purposes. These provisions typically allow the use of a copyright work for the purposes of research or private study, personal or private use, criticism and review, and news reporting. Unfortunately there is no South African case law concerning the fair dealing provisions, and the application of these exceptions remains unclear. This study aims to clarify the extent of application of the fair dealing exceptions to copyright infringement so that courts may be more willing to consider foreign and international law and in doing so develop South African intellectual property law. The social and economic policy considerations underlying the fair dealing exceptions are considered to determine their function. International conventions relating to copyright and neighbouring rights are examined, specifically the provisions allowing exceptions to copyright. The legislation and case law of Australia and the United Kingdom are analysed to determine the proper interpretation and application of these statutory defences. This knowledge is then used to inform South African law. The Copyright Act 98 of 1978 does not contain a fair dealing exception for parody and satire. Australian legislation does contain such an exception, and it is analysed in that context. An exception for parody is proposed for South African law, and the need for and application of this provision is considered. The constitutionality of the proposed exception is evaluated in terms of its impact on the constitutional property rights of copyright owners.
Keywords: Australia; Copyright law; Fair dealing; Fair use; Great Britain; Intellectual property; South Africa; Trademarks

Innovation and Intellectual Property: Strategic IP Management and Economics of Technology - Holgersson, Marcus (Chalmers University of Technology, 2012)
Innovations and technological developments have been recognized for their central importance for economic success and growth at least since the 1930s. Intellectual property (IP) and intellectual property rights (IPRs), such as patents, trade secret rights, and copyrights, have during more recent decades caught increasing attention, and, mainly due to various developments at macro level, IP has become an important source of competitive advantage at micro level in many industries. This has led to an increased importance of strategic IP management, and the related research field has been growing since the late 1990s. This thesis aims to contribute to this growing field, and the first purpose of this thesis is to explore and explain strategic and innovation related IP management practices, and the managerial and economic consequences of such practices. Apart from the growing importance of IP management in general, an increased focus on open and collaborative approaches for creating innovations has led to a need for new and adapted IP management skills. The second purpose of this thesis is therefore to develop managerial and economic frameworks, models, and tools to be used in the intersection between IP management and open innovation practices. These purposes are addressed in a cover paper and six appended research papers of theoretical/conceptual as well as of empirical nature, being based on interviews, questionnaires, patent statistics, and document studies. In connection to the first purpose the results show that, while many small firms have problems with properly benefitting from the patent system, large firms have increasingly developed their IP strategies, especially their patent strategies. The purpose is then not only to appropriate monopolistic returns from innovations but also to govern various forms of open innovation. Large firms were found to in a first step increase their patenting (in terms of quantity), and in a second step focus more on selective, quality-oriented, and internationalized patenting. Additional results show that the internationalization leads to a convergence in managerial choices of output markets for patenting worldwide, in parallel with market and technology diversification. Further, a case from mobile telecommunications illustrates the role of IP management in the governance of open innovation systems. Finally, two cases from the automotive industry illustrate the IP-related problems that arise in connection to divestments and other types of disintegrations (‘IP disassembly problems’), and how IP management can mitigate them. This leads to the second purpose, related to the development of models, tools, and frameworks for IP management in relation to open innovation. First, the thesis provides a conceptual framework of innovation openness, especially pinpointing the role of IPRs. This framework emphasizes three key dimensions of innovation openness: resource distribution, technology governance, and technology accessibility. Second, a framework for managing the IP disassembly problem is presented, enabling increased exit opportunities and decreased transaction costs. Third, a method for determining fair, reasonable, and non-discriminatory royalties in licensing collaborations is developed, applicable to multilateral licensing deals. It stands clear that contemporary IP management is not (and has never been) only about maximizing excludability. Strategic IP management must therefore be developed and integrated with technology and corporate management in order to foster success at the micro level of firms, and thereby also at macro level. Developments in IP management skills (e.g., sourcing, control, commercialization, licensing, valuation, pricing) and IP contracts will then most likely lead to increased efficiency of interorganizational technological relationships and quasi-integrated organizational forms, and thereby also to increased innovativeness and economic development.
ISBN 978-91-7385-761-1 Doktorsavhandlingar vid Chalmers tekniska högskola, Ny serie nr 3442 ISSN 0346-718X
Keywords: Adresse IP; Economie numérique; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Aspects of the nature and online resolution of domain-name disputes - Hurter, Eddie (University of South Africa, 2011)
The thesis analyses selected aspects of domain-name law, mainly from the perspective of trade-mark law. It discusses the evolution of the domain-name system and how it operates as background to a more detailed discussion of the theoretical classification of domain names. The thesis then examines the interplay between trade marks and domain names, and the resolution of domain-name disputes resulting from the inherent tension between these two systems. The main principles of domain-name dispute resolution are identified by way of an analysis of the panel decisions handed down in terms of the international Uniform Dispute Resolution Policy (UDRP) and the South African domain name dispute resolution regulations. This analysis always addresses, too, the extent to which national trade-mark law principles (with reference to the laws of South Africa, the United Kingdom, and the United States of America) apply, and the extent to which this is appropriate.
Keywords: Abusive domain name registration; Cybersquatting; Dispute resolution; Domain names; ICANN; Intellectual property; Internet Corporation for Assigned Names and Numbers; Internet domain names; Nominet Dispute Resolution Service; Trademarks; Typosquatting; WIPO domain name processes; Well known trade marks; World Intellectual Property Organization

Copyright in the digital environment : ontologies of copyright and digital works - Filippi, Primavera De (European University Institute, 2011)
The advent of Internet and digital technologies has radically transformed the way information is being produced and consumed. The consequences for copyright law are twofold. While digital media provide new opportunities for authors to produce and disseminate their works to the public, they simultaneously encourage and facilitate copyright infringement. Traditionally, in order to ensure compliance with the law, the copyright regime could rely upon the properties of physical media to constitute a natural barrier against copyright infringement. As the medium went digital, however, its properties became a catalyst for infringement. Designed for the physical world, the structure of the copyright does not adequately address the issues inherent to digital media. Private regulation therefore came into play in order to resolve the problem. While restrictive licensing agreements combined with technological measures of protection purport to reestablish a technological barrier against copyright infringement, permissive licenses such as Creative Commons purport to reduce the scope of protection granted by default under the law. Although differing in method, these approaches share a common goal: to realign the properties of the work with the properties of the digital medium by readjusting the legal attributes and technical characteristics of digital copies. As a legal concept, however, the notion of a copy must be precisely defined. After performing an ontological analysis of the copyright regime within the scope of the Functional Requirements for Bibliographic Records and the Information Artifact Ontology, the research concludes that physical copies fundamentally differ from their digital counterpart. While the former qualify as a token, the latter qualify as a class that is capable of multiple instantiations. Moreover, given that the identity of a digital copy can no longer be defined by its physical characteristics, it is fundamentally for the copyright license to determine the scope of the copy to which it refers.
Keywords: Copyright; Digital media; Electronic data processing; Intellectual property; Internet

Intellectual Property Law and Competition Law - Patel, Atul; Panda, Auro Aurobinda; Deo, Akshay; Khettry, Siddhartha; Mathew, Sujith Philip (Journal of International Commercial Law and Technology, 2011)
Competition law and intellectual property rights (IPRs) have evolved historically as two separate systems of law. There is a considerable overlap in the goals of the two systems of law because both are aimed at promoting innovation and economic growth. Yet there are also potential conflicts owing to the means used by each system to promote those goals. IP laws generally offer a right of exclusive use and exploitation to provide a reward to the innovator, to provide an incentive to other innovators and to bring into the public domain innovative information that might otherwise remain trade secrets. Competition authorities regulate near monopolies, mergers and commercial agreements with the aim of maintaining effective competition in markets. This article introduces the concept of IPRs and Competition law. It highlights important areas of conflict between the two laws and also deals with the Indian antitrust law. It concludes by trying to harmonize the conflicts.
Keywords: Competencia; Competition law; Intellectual property

The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

Explaining Copyright: The Normative Implications of its Sociotechnical Construction - Nicholson, Scott (Queen’s University, 2008)
The construction of copyright law can be causally explained by two possible types of explanation: dialectical explanations and material explanations. I argue that an adequate causal description of the copyright discourses of Western legal systems must incorporate a material explanation in order to account for many of the general and particular characteristics of the evolution of copyright. As a vast variety of contingent and interactive social and technical conditions have caused the evolution of copyright, we should expect a plausible material explanation to be multifaceted and multi-layered. However, in addition to providing a causal sociohistorical description, a good legal explanation should also seek to include a normative account detailing the moral grounds of the law, or lack thereof. Dialectical explanations can be teleological: they can presuppose that the law is directed towards a perfect legal state and that it is essentially guided by a set of moral ideals. Material explanations, on the other hand, are essentially non-normative and do not explicitly address moral questions. But this does not entail the elimination of moral considerations from material explanations. As I aim to show, we should not address the moral and sociohistorical elements of copyright legal discourses independently because they are causally connected: moral justifications have been rhetorically used by social actors to influence lawmaking processes, and conversely, changes in technical conditions have given rise to sociotechnical formations that enable and structure the norms of copyright. Given this, I propose that lawmakers should adjudicate and legislate from a broad and flexible standpoint. They should not attempt to merely apply old principles to new problems, but should comprehend new moral norms introduced by new conditions, and balance them against the older, more established principles enshrined in traditional intellectual property theories.
QSpace: Queen's Scholarship & Digital Collections
Keywords: Copyright; Intellectual property

A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch University, 2005)
Trade marks are among the most valuable commodities of the modern business world. Adequate protection for trade marks to prevent the misappropriation of their incredible marketing power is therefore important. The aim of this dissertation is to make recommendations regarding the further development of existing South African law regarding the protection of registered trade marks against dilution, particularly by the courts. Current statutory protection is examined and compared with trade-mark law in the United States and the European Union. Although the concept of dilution originated in Germany, most of its development took place in the United States, starting in 1927 with an article by Frank Schechter. Dilution occurs when the awareness that a specific mark signifies a single product from a single source changes to an unmistakable awareness that the same mark signifies various things from various sources. The primary theories as to how dilution occurs are blurring and tarnishment. Although the dilution concept is widely recognised, there is still a debate amongst legal scholars on whether trade marks deserve protection against dilution. The extent of protection that the law gives to trade marks largely depends on the socioeconomic functions that a trade mark is perceived to fulfil. The original source or origin function is protected by the traditional infringement provisions. The identification or distinguishing function, quality function and advertising function subsequently gained recognition. The advertising function is statutorily recognised in various jurisdictions, which prevents trade-mark dilution. Statutory recognition of dilution in the United States first occurred in State law from 1947 onwards. Protection is generally given to distinctive or strong trade marks where a similar mark is used on dissimilar goods in the absence of confusion in such a way that there is a likelihood that the reputation of the senior mark will be injured. The parameters of the concept were developed and refined mainly through case law. Federal protection against dilution was only introduced in 1995. The new Act, although widely welcomed, also brought some unpredictability and interpretation problems. The first statutory dilution protection for trade marks in Europe is found in the Uniform Benelux Trade Marks Act. In 1989 the European Union adopted the Trademark Directive, with the aim of harmonising the legal protection afforded to trade marks. Its "dilution" provisions were incorporated into the United Kingdom's Trade Marks Act of 1994. The sometimes conflicting interpretations of these provisions by the English courts and the Court of Justice of the European Communities are discussed. The South African Act shows a substantial degree of harmony with legislation in the United Kingdom and other European countries. Aspects of the wording of the dilution provisions are however open to interpretation by the courts. Until the end of 2003 there was only one major trade-mark dilution case decided by a South African court, namely SAR v Laugh It OjJPromotions, which is discussed in detail. The dissertation concludes with recommendations to aid South African courts in the future interpretation and application of the dilution provisions. Amendments to the legislation are also proposed to promote greater clarity.
URI: http://hdl.handle.net/10019.1/50239
Keywords: Brand name products; Comparative law; European Union countries; Intellectual property; South Africa; Trademarks; United States